'I have to save this language, it's on the edge like an endangered animal': perceptions of language threat and linguistic mainlandisation in Hong Kong. Issue 4 (21st April 2021) - Hansen Edwards, Jette G.
ABSTRACT: This study examines perceptions of language threat in Hong Kong against a background of increasing political tensions between Hong Kong and the People's Republic of China (PRC). These tensions gained international attention in 2014 during the 79-day protests known as the Umbrella Movement and more recently in 2019 due to the proposed introduction of an extradition treatybetween Hong Kong and mainland China. It is against this politically divisive landscape that the article examines perceptions around Hong Kong's three spoken official languages: English, Cantonese, and Putonghua. Quantitative and qualitative survey data were collected in 2017 from 568 students across 15 tertiary institutions in Hong Kong, with questions probing whether the respondents perceived that Cantonese was under threat, and if so, from which language – Putonghua or English or both. Respondents were also asked whether the current political tensions in Hong Kong were impacting their attitudes towards Cantonese, English, or Putonghua. A series of open-ended questions sought to find out why the respondents held particular perceptions towards these three languages. Gender as well as cultural identification were also examined as previous research has found that they significantly impact language attitudes in Hong Kong.